ANALYSIS OF TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY OF GREEN TEA (Camellia sinensis) WITH VARIATIONS IN TYPE AND BREWING - Salamah, Nina; Widi Astuti, Silvia Ferry; Ar Rahma, Nur Aulia; Guntarti, Any (Universitas Muhammadiyah Magelang, 2024)
Free radicals can react to cause damage when they enter the human body. The use of antioxidants can neutralize free radicals in the body. This study aims to determine the total flavonoid levels and antioxidant activity in premium and original green tea with variations in brewing temperature. Green tea produced by Kulon Progo is brewed with aquadest at 75 ℃ and 100 ℃, and then the filtrate obtained is ground by freeze-drying. Identification of flavonoid compounds using the flavanoid-ammonia vapor color complex. The total flavonoid levels analysis using UV-vis spectrophotometry and antioxidant activity was tested by the DPPH (1,1-diphenyl-2-picrylhydrazil) method. Based on the test results, the highest to lowest total flavonoid levels were premium green tea at 100 ℃ original at 100 ℃, original at 75 ℃, and premium at 75 ℃ (155.095 ± 3.158; 153.333 ± 2.788; 151.7181 ± 4.944; and 148.634 ± 2,095 mgQE/gram extract). The highest to lowest potential antioxidant activity, respectively, is quercetin (flavonoid standard), premium green tea at 100 °C, premium at 75 °C, original at 100 °C, and original at 75 °C, with IC50 values of 3.0692 ± 1.064; 32.359 ± 7.346; 31.502 ± 6.746; 27.527 ± 7.868; and 27.167 ± 1.817 μg/mL. Analysis of the total flavonoids of green tea showed that the highest levels were in premium green tea at a temperature of 100 °C. An antioxidant activity test with the DPPH reagent produced the highest antioxidant potential in premium green tea at 100 °C. So premium green tea at a brewing temperature of 100 °C is more recommended to consumers.